Mortality and functional disability in heat stroke - Alexis Eduardo Higareda-Basilio; Flor Agruel Trujillo-Narvaez; Hiram Javier Jaramillo-Ramirez (Instituto Nacional de Salud Pública, 2019)
[Not available]